Reconceptualising professional learning through knowing-in-practice: a case study of a coaches high performance centre - Phelan, S.; Griffiths, M. (Sports Coaching Review, 2019)
In response to learning development literature that is negative regarding the formal education coaches` encounter, there has been a conceptual/practical shift towards recognising the coaching workplace as a legitimate site for professional knowledge development. Building upon contemporary studies of learning `in situ`, this paper draws upon the theory of practice architectures to provide an innovative language by which to capture the complexity of learning within this context. In doing so, the cultural-discursive, material-economic, and socio-political arrangements of practice are shown to either enable or constrain learning activities. Findings from a 10-month ethnographic study of a high-performance training centre (n= 9 coaches/support staff), highlighted the significant role the macro-structural features of sport, and the inherent `learning culture`, played in determining the learning valued within this context. This study draws attention to the challenges a transient coaching workforce, within a dynamic environment, presents to those attempting to foster learning in this context.